How does migration affect child labor in sending countries? - Mariapia Mendola (IZA World of Labor, 2016)
International labor mobility has resulted in sweeping socio-economic changes in many developing countries. When a family member migrates for work and sends back remittances, household income may rise, and with it investment in children's schooling. Emigration flows may also alter local labor market conditions and wage rates, which can in turn affect children's labor supply. Whether there is more or less child labor as a result of migration may depend on the skill composition of the migrants and on how family members respond to wage changes.
Keywords: O15; 330; international migration; labor market; child labor; developing countries